Studying engagement in educational settings: a mapping review on high-impact academic engagement research - Loyola-Carrillo, Paola; Vega-Muñoz, Alejandro; Salazar-Sepúlveda, Guido; Gil-Marín, Miseldra; Adsuar-Sala, José (Frontiers in Psychology, 2025)
IntroductionAcademic engagement provides opportunities and resources for students to engage in socio-educational interactions and learning. Our study provides an overview of high-impact research in academic engagement and the potential causes of its high valuation in the scientific community.MethodsWe conducted a mapping review using bibliometric analysis of 1,607 articles indexed in Web of Science, processed mainly by VOSviewer software.ResultsThe publication of selected articles grew exponentially year by year, presenting concentration levels of 1% in authorship, 49% in a single country, and 5% in journals, identified as outstanding Keywords plus® central aspects of academic engagement (classroom-social environment and school engagement), in addition, 6% were in highly cited articles.ConclusionThese highly cited articles (6%) are associated with authors with high levels of publication. The most cited current topics relate to the motivation and emotional aspects of academic engagement.